Outcome of Non-operative Management of Perforated Peptic Ulcer Disease (Journal of Surgical Sciences, 2020)
Background: Peptic ulcer perforation management is still an enigma. Though the overall incidence has been reduced worldwide due to wide use of anti-ulcerants, still it is not uncommon. But there is a debate regarding its conservative management over surgical management.Objective: To determine whether surgery could be avoided in selected patients with perforated peptic ulcer diseaseMethods: This study was conducted in the department of Surgery of Sir Salimullah Medical College and Mitford Hospital during the period from 1st March 2016 to 31st August 2016. After approval from the institutional ethics committee, 30 patients of suspected perforated peptic ulcer disease were successively assigned in this study on clinical and radiological basis. All were given non-operative regimen up to 24 hours. Then they were closely monitored to see improvement of clinical condition or development of any complication. Non-operative treatment was abandoned if the patient failed to improve or deteriorated within 24 hours of non-operative treatment. The data were collected by active participation of patients’ interview in preformed data collection sheet. Results: The data analysis of 30 patients yielded that most of them (86.67%) recovered well after receiving non-operative management, whereas only 4 patients (13.33%) showed no progression and were treated by laparotomy. 73.08% patients with uneventful outcome left the hospital within 10 days of admission and the others were a little late to leave.Conclusion: Patients with perforated peptic ulcer disease can be effectively treated by conservative approach in properly selected cases by proper monitoring under strict supervision of an experienced consultant.Journal of Surgical Sciences (2018) Vol. 22 (2) : 95-98